Delayed Sternal Closure after Congenital Heart Surgery in Infants: Postoperative Course - Yakimishen, E.; Petrenko, A.; Boyko, S.; Rudenko, M.; Prokopovych, L. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Delayed sternal closure in infants and children of the first months of life after the correction of complex congenital heart defects (CHD) can increase cardiac output. This is a forced measure due to the development of unstable hemodynamics, capillary leak syndrome and myocardial edema, as the sternotomy wound closure in the early postoperative period provides a compression effect on the function of the myocardium. The aim. To evaluate mortality and to detect predictors of adverse outcome as well as the incidence of non-cardiac complications in delayed sternal closure after surgical repair of CHD. Materials and methods. Twenty two children were studied. Six children died. Anesthetic management was provided using propofol (4–6 mg/kg/h) and fentanyl (5–10 μg/kg/h) infusions. Modified ultrafiltration was applied at the end of assisted circulation in all the cases. Sternal closure was performed on average on day 3 ± 2 after surgery. Results. Mortality odds ratio (OR) in patients with the mean arterial pressure (MAP) < 35 mmHg was 3.7; mortality OR in patients with SVO2 < 40 % was 0.94; mortality OR in patients with blood lactate > 10 mmol/L in the first three days of postoperative intensive care was 2.1. Conclusions. Delayed sternal closure is an acceptable method of maintaining cardiac output in young infants with CHD in postoperative period. High blood lactate (> 10 mmol/L) and especially its further growth, as well as MAP < 35 mmHg, can predict adverse outcomes of cardiac surgery with open sternotomy.